Analisis Kinerja Keuangan Terhadap Harga Saham Emiten Sektor Transportasi Logistik 2021-2023 - Nurul Arum Puspita; Rudi Kurniawan Lenni Yovita; Pradana Jati Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the impact of financial performance on stock price movements of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The financial performance variables examined include Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Earnings Per Share (EPS). The study selected 10 companies with the largest total assets using purposive sampling. Data were obtained from quarterly financial reports and the closing stock prices at the end of each trading period. The analysis employed multiple linear regression along with classical assumption tests. The results indicate that EPS, NPM, ROE, and ROA each have a significant positive effect on stock prices, while DER shows a negative but not statistically significant relationship. Overall, the independent variables significantly influence stock prices simultaneously, as reflected by an Adjusted R² of 84.3%.